2009
DOI: 10.1080/08927010902875113
|View full text |Cite
|
Sign up to set email alerts
|

Purification and partial amino acid sequence analysis of the larval settlement-inducing pheromone from adult extracts of the barnacle, Balanus amphitrite (=Amphibalanus amphitrite)

Abstract: A previously undescribed larval settlement-inducing protein was purified from adult extracts of the barnacle, Balanus amphitrite (=Amphibalanus amphitrite). Results of SDS-PAGE indicated that the relative molecular mass of the protein in reduced and denatured form is 31,600 +/- 500 kDa, and that it is distinct from the Settlement Inducing Protein Complex (SIPC) which has previously been determined as a larval settlement-inducing pheromone. The N-terminal 33-residue sequence of the intact protein showed no simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 22 publications
4
31
0
1
Order By: Relevance
“…In particular, the involvement of pheromones, hormones, neurotransmitters and proteins in regulating larval settlement of B. amphitrite has been intensively studied (e.g. Clare et al, 1995;Yamamoto et al, 1995;Yamamoto et al, 1997;Matsumura et al, 1998b;Matsumura et al, 1998c;Yamamoto et al, 1999;Delort et al, 2000;Endo et al, 2009;Gallus et al, 2010). Based on these results, it has been suggested that signaling transduction systems are likely involved in transmitting and/or translating these exogenous signals to endogenous effectors, resulting in the initiation of larval settlement (Clare et al, 1995;Yamamoto et al, 1997;Yamamoto et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the involvement of pheromones, hormones, neurotransmitters and proteins in regulating larval settlement of B. amphitrite has been intensively studied (e.g. Clare et al, 1995;Yamamoto et al, 1995;Yamamoto et al, 1997;Matsumura et al, 1998b;Matsumura et al, 1998c;Yamamoto et al, 1999;Delort et al, 2000;Endo et al, 2009;Gallus et al, 2010). Based on these results, it has been suggested that signaling transduction systems are likely involved in transmitting and/or translating these exogenous signals to endogenous effectors, resulting in the initiation of larval settlement (Clare et al, 1995;Yamamoto et al, 1997;Yamamoto et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed work at the growth interface shows lipids are secreted beyond the base and act as a surface-cleaning fluid followed by the deposition of proteins some of which might be delivered through capillaries and ducts (Burden et al, 2012;Golden et al, 2016;Fears et al, 2018). Numerous cement proteins have been identified from solubilizing hardened glue, as well as two similar groups of cuticular proteins, settlement inducing protein complex (SIPC) and MULTIFUNCin (Kamino and Shizuri, 1998;Matsumura et al, 1998a;Kamino, 2001;Dreanno et al, 2006a;Ferrier et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In many barnacle species, gregarious settlement is also essential to ensure that mating neighbors are sufficiently close once the individual becomes an adult. Since the 1950s, cyprid responses to chemical cues from conspecifics have been thought to be one of the most important mechanisms leading to conspecific gregarious settlement in barnacles, and two types of proteinaceous settlement cues have been purified from the adult B. amphitrite (Matsumura et al, 1998a;Dreanno et al, 2006a;Endo et al, 2009). However, the effective area of these chemical cues in the ocean may be limited (Elbourne and Clare, 2010), and other specific factors are possibly involved in their gregarious settlement behavior.…”
Section: Discussionmentioning
confidence: 99%
“…SIPC was suggested to be involved in chemical communication between larvae as well as between larvae and adults (Matsumura et al, 1998c;Dreanno et al, 2006b). In addition, waterborne chemical cues have been proposed to induce larval settlement , and a 32 kDa protein was recently identified as a waterborne settlement pheromone released by adult B. amphitrite (Endo et al, 2009). However, these chemical cues may attract cyprids only in very close proximity to adults (Elbourne and Clare, 2010).…”
Section: Introductionmentioning
confidence: 99%